Efeitos da perda de peso induzida pela cirurgia bariátrica sobre a função respiratória - Freitas, Cledna da Rocha Barreto de (2011)
Background: Obesity leads to alteration of lung volumes and capacities due to accumulation of fat in the chest wall and abdomen. Few studies have shown that weight loss induced by surgery improves lung function. Our objective was to evaluate the anthropometric development, pulmonary function, respiratory muscle, strength and endurance after weight loss induced by bariatric surgery. Methods: We evaluated in pre and post operative period variables of weight, BMI, NC, WHR and spirometric and respiratory pressure. Results: 39 subjects were evaluated, with age mean 35.9 ± 10.9 years, predominantly by women (76.3%). The weight mean decreased from 124.8 ± 17.5 kg to 88.8 ± 14.28 kg in post operative. The mean BMI ranged from 47,9 ± 5,6 Kg/m² to 34,3 ± 4,75 Kg/m². There was a significant increase in FVC from 3,63 ± 0,94 to 4,01±1,03, FEV1 from 3,03 ± 0,72 to 3,39 ± 0,85, FEF 25-75% from 3,41 ± 0,72 to 3,82 ± 0,94, PEF from 6,56 ± 1,47 to 7,81 ± 1,69, ERV from 0,35 ± 0,39 to 0,66 ± 0,38, MVV ranged from 103,43 ± 22,21 to 137,27 ± 29,84, all of them to p<0,01. The MIP and MEP showed no significant difference in pre and post operative. It was noted that for every centimeter reduced in neck circumference, an increase of 0.06 in FVC and 5.98 in MVV is observed. This is also observed in weight and BMI. Conclusion: We conclude that weight loss induced by bariatric surgery in obese provides a significant improvement in lung function and reduction of fat around the neck is more important in the generation of lung volume than the reduction of BMI